DETERMINASI MINAT MAHASISWA AKUNTANSI MEMILIH KARIR MENJADI AKUNTAN PUBLIK - Pujiyati, Darmi; Mranani, Muji; Waharini, Faqiatul Mariya (Universitas Muhammadiyah Magelang, 2018)
This study aims to analyze the determination of interest accounting students choose a career to be a public accountant. Data in this research is primary data. The population used in this study are S1 accounting students at the Muhammadiyah University of Magelang and Ahmad Dahlan University. This study uses a quantitative approach, in which the research is in the form of associative research with the type of causality. The sample of this research is 165 students by using purposive sampling technique. The questionnaire returned and met the criteria of 149 copies. The results of this study indicate that the percentage of the effect of labor market considerations, professional recognition, social values, work environment, personalities and financial rewards can explain the interest of accounting students to choose a career as a public accountant. The variables of labor market consideration, professional recognition, social values, work environment, personality and financial reward can explain the interest of accounting students to choose a career as a public accountant and this research model can be said to be good (fit). Test results show that labor market considerations, professional recognition, work environment and personality have a positive effect on accounting student's interest in choosing a career as a public accountant. While social values ​​and financial rewards do not positively affect the interests of accounting students choose a career to be a public accountant.